1999
DOI: 10.1017/s0967199499000519
|View full text |Cite
|
Sign up to set email alerts
|

Fate of genetically marked mitochondrial DNA from spermatocytes microinjected into mouse zygotes

Abstract: Cytoplasts from single spermatocytes of NZB/BinJ mice were separated from the nuclei and individually microinjected into B6D2F1 (C57BL/6 × DNBA/2J) hybrid embryos at the pronuclear stage (20 h after hCG injection). Of 363 zygotes injected, 311 (86%) survived and developed. From these experiments, we transferred 222 embryos into 20 pseudopregnant recipients. Eighteen (90%) became pregnant and 82 pups were born (37% of transfers). Mitochondrial DNA (mt DNA) from the NZB/BinJ strain lacks a RsaI restriction site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In ROSI, the injected round spermatids should carry mitochondria that are already imprinted with ubiquitin, and the initial studies in mice indeed suggest that their spermatid mitochondria can be recognized and eliminated by egg cytoplasm [65]. Similarly, spermatocyte mitochondria and mtDNA became undetectable when spermatocyte cytoplasts were injected into mouse pronuclear embryos [66]. With regard to cloning, it was suggested that the mismatched mitochondrial gene products may contribute to the high mortality of cloned offspring [67].…”
Section: Discussionmentioning
confidence: 99%
“…In ROSI, the injected round spermatids should carry mitochondria that are already imprinted with ubiquitin, and the initial studies in mice indeed suggest that their spermatid mitochondria can be recognized and eliminated by egg cytoplasm [65]. Similarly, spermatocyte mitochondria and mtDNA became undetectable when spermatocyte cytoplasts were injected into mouse pronuclear embryos [66]. With regard to cloning, it was suggested that the mismatched mitochondrial gene products may contribute to the high mortality of cloned offspring [67].…”
Section: Discussionmentioning
confidence: 99%
“…Spermatid-derived mtDNA, however, was detectable by real-time PCR up to the blastocyst stage, but had disappeared by the time of birth (Shitara et al 2000). Primary spermatocyte mitochondria, in contrast, dispersed rapidly throughout the oocyte cytoplasm (Cummins et al 1998a), but 292 S Hiendleder and E Wolf spermatocyte mtDNA could also not be detected in different organs of offspring at a detection level of ‡ 1-5% (Cummins et al 1999). However, these data are at variance with two other studies that detected paternal mtDNA in human embryos derived from IVF and ICSI by a highly sensitive paternal allele-specific nested PCR.…”
Section: Mtdna Inheritance In Embryo Technologiesmentioning
confidence: 95%
“…Primary spermatocyte mitochondria, in contrast, dispersed rapidly throughout the oocyte cytoplasm (Cummins et al. 1998a), but spermatocyte mtDNA could also not be detected in different organs of offspring at a detection level of ≥ 1–5% (Cummins et al. 1999).…”
Section: In Vitro Fertilization and Intracytoplasmic Sperm Injectionmentioning
confidence: 99%
“…Based on the previous points (1)(2)(3)(4)(5) and on studies of the scientists and their wrong assumptions, theories, contradictions, and on known facts I wish to suggest the following 1-Paternal Y sperm has no mitochondria at all (pure maleness-masculinity).…”
Section: Alfleesy Suggestionmentioning
confidence: 99%